PIERRE GASSENDI (ABINGDON)
1 online resource
Keywords: Pierre Gassendi (1592-1655) was a major figure in seventeenth-century philosophy and science and his works contributed to shaping Western intellectual identity. Among new philosophers, he was considered Descartes's main rival, and he belonged to the first rank of those attempting to carve out an alternative to Aristotelian philosophy. In his writings, he promoted a revival of atomism and Epicureanism within a Christian framework, and advocated an empiricist and probabilistic epistemology which was to have a major impact on later thinkers such as Locke and Newton. He is moreover important for his astronomical work, for his defense of Galileo's mechanics and cosmology, and for his activity as a biographer. Given the importance of Gassendi for the history of science and philosophy, it is surprising to see that he has been largely ignored in the Anglophone world. This collection of essays constitutes the first book on Gassendi in the English language that covers his biography, bibliography, and all aspects of his work. The book is divided into three parts. Part I offers a reconstruction of the genesis of Gassendi's Epicurean project, an overview of his biography, and analyses of Gassendi's early attacks on Aristotle, of his advocacy of Epicurean philosophy, and his relation to the skeptical tradition and to Cicero's thought. Part II addresses Gassendi as a participant in seventeenth-century philosophical and scientific debates, focusing especially on his controversies with Descartes and Fludd. Part III explores Gassendi's contributions to logic, theories of space and time, mechanics, astronomy, cosmology, and the study of living beings, and presents the reception of Gassendi's thought in England. This book is an essential resource for scholars and upper-level students of early modern philosophy, intellectual history, and the history of science who want to get acquainted with Pierre Gassendi as a major philosopher and intellectual figure of the early modern period.